Telecommunications reform and efficiency performance: do good institutions matter? - Mohamad, Noorihsan (Elsevier, 2014)
Until recently, most studies investigating telecommunication reforms performance have failed to incorporate the importance of institutions into the empirical analysis. This study highlights the importance of institutional governance on telecommunications efficiency and provides empirical results for the impact of institutions on reform outcomes. It provides significant evidence that the institutional environment in which reform progress takes place is an important determinant for successful reform. This study uses the stochastic distance function approach to capture the role of institutions in explaining efficiency differences across 70 countries. The empirical analysis reveals that policy stability in the form of separation of powers and substantive checks and balances on executive power is the most important aspect for efficiency improvement through reform. Independently, legal integrity improves telecommunications efficiency through privatization, while greater freedom from corruption influences the effectiveness of a regulatory body.